Role of autophagy in triacylglycerol biosynthesis in Chlamydomonas reinhardtii revealed by chemical inducer and inhibitors - Wanvisa Pugkaew (2019)
© 2017, Springer Science+Business Media Dordrecht. Autophagy mediates degradation and recycling of cellular components and plays an important role in senescence and adaptive responses to biotic and abiotic stresses. Nutrient deprivation has been shown to trigger triacylglycerol (TAG) accumulation and also induces autophagy in various green algae. However, the functional relationship between TAG metabolism and autophagy remains unclear. To gain preliminary evidence supporting a role of autophagy in TAG synthesis, Chlamydomonas reinhardtii CC-2686 was grown in Tris-acetate phosphate medium with or without nitrogen and treated with an autophagy inducer (rapamycin) or inhibitors (wortmannin, 3-methyladenine, and bafilomycin A1). Fluorescence microscopic analysis of Nile red-stained cells following 72-h treatments showed that rapamycin induced accumulation of subcellular lipid droplets which are storage sites of TAG. Rapamycin treatment in combination with nitrogen starvation led to a greater abundance of lipid droplets. Wortmannin and bafilomycin A1, but not 3-methyladenine, inhibited lipid droplet accumulation in rapamycin-treated cells and to a less extent in nitrogen-depleted cells. These results suggested that autophagy contributes to TAG synthesis in C. reinhardtii, but is not a necessary process. Autophagy induction may also be used to further enhance TAG accumulation in microalgae under nutrient deprivation.